2010
DOI: 10.1111/j.1465-3362.2009.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug injecting in patients in New Zealand Methadone Maintenance Treatment programs: An anonymous survey

Abstract: Many individuals on MMT continue to inject their methadone. In this sample, the frequency of injection of methadone did not correlate with prescribed dose or takeaway arrangements. The beneficial impact of time on the programme emphasises the importance of retention in treatment. It is suggested that these results also indicate a need for routine education concerning safe injecting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The main finding of this study was that, in keeping with previous reports [1,9,11,14,18,19,31,34], nearly one third of patients under OMT reported misuse, this outcome not being influenced by OMT type or dosage in the multivariate model. In accordance with previous studies [35,36], age class was significantly and inversely associated with misuse, suggesting that younger patients under OMT should be more strictly monitored.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The main finding of this study was that, in keeping with previous reports [1,9,11,14,18,19,31,34], nearly one third of patients under OMT reported misuse, this outcome not being influenced by OMT type or dosage in the multivariate model. In accordance with previous studies [35,36], age class was significantly and inversely associated with misuse, suggesting that younger patients under OMT should be more strictly monitored.…”
Section: Discussionsupporting
confidence: 73%
“…Data on the prevalence of MET and BUP injection is inconsistent across studies, with figures ranging from 5.0 to 35.8% for MET and from 9.1 to 46.5% for BUP [1,9,11,12,14,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may self-administer OMT by intravenous route because of the shorter time to peak plasma level and the higher reinforcing effect [3]. Several studies reported intravenous OMT misuse with a prevalence of 5-36% for MET and 9-47% for BUP [4][5][6][7][8][9][10][11][12][13]. Sublingual or soluble film BUP-NLX was marketed, assuming that it would reduce the risk of diversion and misuse [14,15], but post-marketing studies showed similar rates of injections for MET, BUP and BUP-NLX [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some injecting drug users (IDU) in opioid substitution treatment (OST) inject while in treatment (Judson et al, 2010;Li et al, 2012), and consequently, continue to use needle exchange programmes (NEP) services (Gervasoni et al, 2012;Kerr et al, 2005). Continued drug use is cited as evidence of the failure of OST (Gyngell, 2011), and it is one of the reasons why the UK government, since 2010, has moved towards a drug strategy that emphasises rehabilitation with the aim of abstinence rather than OST (UK Government, 2010).…”
Section: Introductionmentioning
confidence: 99%